Effectiveness of Implementation of Independent Curriculum in Junior High School Level of Ende District - Natalia Peni; Melania Priska; Lusia Valentina Bupu (Postgraduate, University of Mataram, 2025)
The school mover program is one form of realization of Indonesia's educational vision of creating a competitive, independent, and character-based advanced Indonesia through the creation of the image of Pancasila students. This study aims to determine the effectiveness of the implementation of the independent curriculum in junior high school mover schools (SMP) in Ende district. This study is a type of qualitative descriptive research, where data is collected using discussion and interview methods. Based on the research that has been conducted, it was found that the implementation of the independent curriculum in junior high school mover schools in Ende district has been running effectively in two schools, namely SMPK Frateran Ndao Ende and SMPN 2 Wolowaru. At the same time, SMPN 4 Wolowaru, SMPN 5 Wolowaru, SMPS Kelimutu, and SMP Muhammadiyah Ende have not fully achieved the 8 aspects of the implementation of the independent curriculum. This is due to the lack of understanding of human resources in educational units, facilities, and infrastructure, differences in the level of readiness of educational units, and the lack of collaboration and intensive mentoring.